Lipid and pleiotropic effects of atorvastatin in patients with acute coronary syndrome - A. A. Yalymov; G G Shekhyan; A. A. Bylyeva; V. S. Zadionchenko (Кардиоваскулярная терапия и профилактика)
Aim. To study the effects of an HMG-CoA reductase inhibitor atorvastatin in patients with acute coronary syndrome (ACS).Material and methods. The study included 116 ACS patients, divided into two comparable groups. Total follow-up time was 180±7 days.Results. In 6 months of the follow-up, the patients receiving atorvastatin demonstrated better clinical effectiveness, left ventricular hypertrophy regression, ejection fraction increase by 16,5% (р<0,05), improved microcirculation and endothelial function. Atorvastatin was also linked to reduced incidence and duration of ischemic episodes and lower incidence of cardiac arrhythmias. Only the patients receiving atorvastatin achieved target levels of blood lipids and demonstrated significant improvement in blood rheology and coagulation. In the atorvastatin group, the levels of von Willebrand factor and C-reactive protein were by 28,8% (р<0,01) and 60,2% (p<0,001) lower than those in the control group, respectively.Conclusion. Atorvastatin improved endothelial function, myocardial perfusion, and central and peripheral hemodynamics in ACS patients, which facilitated a less severe clinical course of the disease.